Hypoglycaemic haemiparesis. (15th October 2013) - Kirresh, Othman; Kamara, Achmed; Samadian, Samad
Abstract : Hypoglycaemic haemiparesis (HH) is an uncommon but important presentation to the emergency department, and it often mimics stroke and is therefore frequently misdiagnosed by clinicians. The mechanism of haemiparesis is not fully understood. This case outlines a diabetic elderly woman, who had been having frequent hypoglycaemic episodes and presented to paramedics with hypoglycaemia associated with a right-sided haemiparesis. She was immediately transferred to the local stroke centre after presenting to the emergency department. CT and MRI did not fit in with her presenting neurology. Her weakness resolved, after normoglycaemia was achieved with dextrose infusion; however, she was reported to be more sleepy and drowsy than usual. After extensive and costly investigations during her prolonged inpatient stay, her unifying diagnosis was an HH which triggered of a hypoactive delirium.